Emergence of polymyxin B-resistant Acinetobacter baumannii in hospitals in Rio de Janeiro - Gabrielle L. Genteluci; Daniela B. C. Gomes; Maria José de Souza; Karyne R. Carvalho; Maria Helena S. Villas-Bôas
ABSTRACT Introduction: Acinetobacter baumannii has been considered a prevalent pathogen in hospitals, raising concern in the medical community due to its broad spectrum of antimicrobial resistance. Since it is a subject that arouses much interest, it has been increasingly studied. Due to the emergence of multidrug-resistant (MDR) Gram-negative bacteria, the use of polymyxins was reestablished. The polymyxins have been considered the only option for the treatment of severe infections caused by MDR A. baumannii. Objective: To investigate the susceptibility profile of A. baumannii to polymyxin B. Material and method: 92 clinical isolates from two public hospitals in the Rio de Janeiro city were studied using broth microdilution method. Results: Most of the isolates were resistant to polymyxin B, 81.5% (n = 75), and minimum inhibitory concentration (MIC) values ranged between 4-64 mcg/ml. Conclusion: These results are a concern since currently the polymyxins have been considered the most effective therapeutic option against MDR isolates of A. baumannii.